2015
DOI: 10.1038/nprot.2015.067
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo generation and characterization of Pseudomonas aeruginosa biofilm–dispersed cells via c-di-GMP manipulation

Abstract: Bis-(3'-5')-cyclic dimeric guanosine monophosphate (c-di-GMP) is a global secondary bacterial messenger that controls the formation of drug-resistant multicellular biofilms. Lowering the intracellular c-di-GMP content can disperse biofilms, and it is proposed as a biofilm eradication strategy. However, freshly dispersed biofilm cells exhibit a physiology distinct from biofilm and planktonic cells, and they might have a clinically relevant role in infections. Here we present in vitro and in vivo protocols for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 56 publications
2
59
0
Order By: Relevance
“…In total, 200 µl of cell culture was then transferred into each well of a 96-well plate (triplicates). As previously described [13], the OD 600 and pyoverdine fluorescence (excitation 400 nm/emission 460 nm) were measured using the Tecan microplate reader, and the relative fluorescence intensity count calculated by dividing pyoverdine fluorescence values by OD 600 values. Three independent experiments were performed in triplicate, one-way ANOVA and Student's t -tests were used to determine statistical significance and the results were shown as the mean ± s.d.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 200 µl of cell culture was then transferred into each well of a 96-well plate (triplicates). As previously described [13], the OD 600 and pyoverdine fluorescence (excitation 400 nm/emission 460 nm) were measured using the Tecan microplate reader, and the relative fluorescence intensity count calculated by dividing pyoverdine fluorescence values by OD 600 values. Three independent experiments were performed in triplicate, one-way ANOVA and Student's t -tests were used to determine statistical significance and the results were shown as the mean ± s.d.…”
Section: Methodsmentioning
confidence: 99%
“…By monitoring the expression level of biomarkers specific to the P. aeruginosa dispersal state ( pvdA and cdrA ), Chua et al . showed that the dispersal state can be maintained in harsh nutritional conditions, but that addition of fresh medium induces reversion to the planktonic mode of growth within 2 hours (Chua et al ., ).…”
Section: Methodological Guidelines For Characterization Of Biofilm DImentioning
confidence: 99%
“…In P. aeruginosa, dispersion upon exposure to NO and elevated nutrient concentrations has been linked to the reduction of the cellular c-di-GMP levels, requiring the PDEs DipA, NbdA, and RbdA [40,51,52,59]. The finding of dispersed cells being characterized by reduced c-di-GMP levels has led to the hypothesis that dispersed cells can be generated by reducing the intracellular c-di-GMP content through modulation of PDEs [60]. In P. putida and P. fluorescens , the large adhesive outer-membrane protein LapA mediates attachment to surfaces and matrix components and is required for the transition from reversible to irreversible attachment [41,61-63].…”
Section: A Tale Of C-di-gmp Modulationmentioning
confidence: 99%